Relação do índice de seca de Palmer com a produtividade do café no estado do Espírito Santo e da soja nos estados de Mato Grosso, Paraná e Rio Grande do Sul - Silva, Vitor Heringer (2016)
Drought is one of the climate phenomena that cause most damage in agriculture influencing negatively the socio-economic development. It occurs when precipitation has values below the climatological normal for a given region. The diagnosis of dry can be do